Efficacy and safety of breast radiothermometry in the differential diagnosis of breast lesions - Caferova, Sahnaz; Uysal, Fatma; Balcı, Pınar; Saydam, Serdar; Canda, Tülay (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : The aim of this study is to research the contribution of radiothermometry (RTM) to the characterization of breast masses, the differentiation of malignant-benign masses and diagnosis of early stage breast cancer. Material and methods : This prospective study comprised 182 cases of patients diagnosed with a breast mass and a control group of 55 cases: a total of 237. Results : When histopathology is accepted as the gold standard among diagnostic methods, the sensitivity, specificity, and positive-negative predictive value for RTM were 90.9%, 20.8%, 61.2% and 62.5%, respectively. Consistency was 0.129. When compared with mammography the same values for RTM examination are 87%, 81.4%, 58% and 95.5%. Consistency was 0.582. Evaluating with respect to size of the mass accepting mammography as the gold standard, RTM examination had sensitivity, specificity, positive and negative predictive values for masses 2 cm and above of 88.9%, 83.3%, 88.9% and 83.3%. Consistency was 0.722. The consistency of RTM for lesion diagnosis in BI-RADS II breast structure is higher than the consistency of mammography. Conclusions : Identification of lesions in the breast and presence of microcalcification by RTM shows that it is more trustworthy compared to mammography. When compared with mammography the validity results for RTM show there is a good level of conformity between the two methods. When evaluated based on the area below the ROC cure and compared to mammography, RTM is sufficiently successful at evaluating positive and negative cases.